Qiyâm al-‘Ijtimâ’iyyah fî Syi’r Abî al-‘Atâhiyyah - Latif, Abdul; Rodhy Harisca; Muzhillah Ar Alqurbani (Postgraduate of IAIN Metro Lampung Indonesia, 2022)
Abu al-‘Atahiyah was famous for his ascetical poetry, but the researcher found that in Abu al-‘Atahiyah’s anthology, not all of his poems go with the ascetical theme’s only. Rather, there are also life values, such as social values ​​that establish other human foundations that spread bonds of mercy, love, tolerance, kindness, cooperation, observance of conscience, fear of God and other meanings. The parameters of the human formulation of society are defined in the Islamic conception. The theory used in this research is the theory of life values ​​by Noeng Muhadjir. The approach used in this research is the pragmatic approach. This approach prove that a literature work is a tool to achieve the aims of the creator of literature works, in addition to pleasure or entertainment also for the sake of enlightenment and education. This research found there are sixteen social values, and these social values show that Abu al-‘Atahiyah, who is known as a religious poet, is also a poet who pays attention to social life.